Contact lens-related keratitis due to an emerging pathogen Alcaligenes faecalis - Venugopal Anitha; Avani Soni; Aditya Sanjeev Ghorpade; Meenakshi Ravindran; Uma Rani (Oman Journal of Ophthalmology)
This case report highlights a rare case of contact lens-related keratitis (CLRK) caused by the emerging pathogen Alcaligenes faecalis, which underscores the growing diversity of microorganisms implicated in ocular infections. A 28-year-old female, who had been using yearly disposable contact lenses (CLs) for the past 8 years without prior complications, developed peripheral corneal infiltrates. The infiltrates were attributed to the chronic use of CLs. Corneal scraping and CL culture results identified A. faecalis as the causative organism, a rare and novel cause of keratitis in CL users. The patient was treated promptly with broad-spectrum topical antibiotics, leading to a full resolution of the infiltrates. This is likely the first documented case of CLRK caused by A. faecalis. While A. faecalis belongs to the Pseudomonadaceae family, it did not manifest as a typical aggressive infection, suggesting a potentially less virulent course in CLRK. This case adds to the growing awareness of nonconventional pathogens in ocular infections and highlights the importance of early detection and treatment to prevent more severe outcomes.